Serum Levels of Proinflammatory Lipid Mediators and Specialized Proresolving Molecules Are Increased in Patients With Severe Acute Respiratory Syndrome Coronavirus 2 and Correlate With Markers of the Adaptive Immune Response. (3rd January 2022) - Turnbull, James; Jha, Rakesh R; Ortori, Catherine A; Lunt, Eleanor; Tighe, Patrick J; Irving, William L; Gohir, Sameer A; Kim, Dong-Hyun; Valdes, Ana M; Tarr, Alexander W; Barrett, David A; Chapman, Victoria
Abstract: Background: Specialized proresolution molecules (SPMs) halt the transition to chronic pathogenic inflammation. We aimed to quantify serum levels of pro- and anti-inflammatory bioactive lipids in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) patients, and to identify potential relationships with innate responses and clinical outcome. Methods: Serum from 50 hospital admitted inpatients (22 female, 28 male) with confirmed symptomatic SARS-CoV-2 infection and 94 age- and sex-matched controls collected prior to the pandemic (SARS-CoV-2 negative), were processed for quantification of bioactive lipids and anti-nucleocapsid and anti-spike quantitative binding assays. Results: SARS-CoV-2 serum had significantly higher concentrations of omega-6–derived proinflammatory lipids and omega-6– and omega-3–derived SPMs, compared to the age- and sex-matched SARS-CoV-2–negative group, which were not markedly altered by age or sex. There were significant positive correlations between SPMs, proinflammatory bioactive lipids, and anti-spike antibody binding. Levels of some SPMs were significantly higher in patients with an anti-spike antibody value >0.5. Levels of linoleic acid and 5, 6-dihydroxy-8Z, 11Z, 14Z-eicosatrienoic acid were significantly lower in SARS-CoV-2 patients who died. Conclusions: SARS-CoV-2 infection was associated with increased levels of SPMs and other pro- and anti-inflammatory bioactive lipids, supporting the future investigation of the underlying enzymatic pathways, which may inform the development of novel treatments. Abstract : Serum levels of pro- and anti-inflammatory lipid mediators were increased in severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) hospitalized patients compared with age- and sex-matched SARS-CoV-2–negative controls; some lipid mediators were significantly correlated with anti-spike and anti-nucleocapsid binding, measures of adaptive immune response.